Intravascular Foreign Bodies Retrieval: Navigating Differences From Childhood to Adulthood - Yaseen, Munaf Jarallah; Akram, Nabeeha Najatee; Nori, Wassan (Scripta Medica, 2025)
Background/Aim: The increasing number of cardiovascular procedures is coupled with higher cardiovascular foreign bodies (FB) embolisation into the circulation. Aim of this study was to analyse centre’s experience with percutaneous retrieval of FB, emphasising the differences between paediatrics and adults and highlighting failure-related parametres. Methods: A retrospective analysis of patients who underwent percutaneous retrieval FB in the heart and major blood vessels from February 2013 to April 2024 in the catheterisation lab at a specialised cardiovascular centre was performed. Data were subdivided into two groups: paediatric and adult. A collection was made of patient demographic and FB details, including type, site, the reason for introduction, duration of impaction, details of retrieval procedure including access site, types of catheters, device and sheath used, the time needed for extraction and whether the retrieval was successful. Results: Twenty-two patients were included, 15 (68.2 %) adults and 7 (31.8 %) paediatric patients. The most common FB retrieved was a guide wire 7 (33 %) followed by an atrial septal occluder 6 (29 %). The right femoral artery was commonly accessed in both subgroups. Snare techniques were used in all patients. There were no complications or deaths reported. Overall procedure success was 18 cases (81.8 %), while the procedure failed in 4 (18.2 %) cases and those patients were referred to open surgery. No statistically significant differences were found between the patient’s age, gender, the type of FB, the site of FB and the duration of FB impaction concerning the outcome of the procedure. Conclusion: Percutaneous retrieval of cardiovascular FB is a safe, successful alternative to surgery. The success rate was comparable between adult and paediatric patients.